Kiwifruit allergy across Europe: clinical manifestation and IgE recognition patterns to kiwifruit allergens - Le, T. M.; Bublin, M.; Breiteneder, H.; Fernández-Rivas, M.; Asero, R.; Ballmer-Weber, B.; Barreales, L.; Bures, P.; Belohlavkova, S.; De Blay, F.; Clausen, M.; Dubakiene, R.; et al. (J Allergy Clin Immunol, 2013)
Kiwifruit is a common cause of food allergy. Symptoms range from mild to anaphylactic reactions.|We sought to elucidate geographic differences across Europe regarding clinical patterns and sensitization to kiwifruit allergens. Factors associated with the severity of kiwifruit allergy were identified, and the diagnostic performance of specific kiwifruit allergens was investigated.|This study was part of EuroPrevall, a multicenter European study investigating several aspects of food allergy. Three hundred eleven patients with kiwifruit allergy from 12 countries representing 4 climatic regions were included. Specific IgE to 6 allergens (Act d 1, Act d 2, Act d 5, Act d 8, Act d 9, and Act d 10) and kiwifruit extract were tested by using ImmunoCAP.|Patients from Iceland were mainly sensitized to Act d 1 (32%), those from western/central and eastern Europe were mainly sensitized to Act d 8 (pathogenesis-related class 10 protein, 58% and 44%, respectively), and those from southern Europe were mainly sensitized to Act d 9 (profilin, 31%) and Act d 10 (nonspecific lipid transfer protein, 22%). Sensitization to Act d 1 and living in Iceland were independently and significantly associated with severe kiwifruit allergy (odds ratio, 3.98 [P = .003] and 5.60 [P < .001], respectively). Using a panel of 6 kiwifruit allergens in ImmunoCAP increased the diagnostic sensitivity to 65% compared with 20% for skin prick tests and 46% ImmunoCAP using kiwi extract.|Kiwifruit allergen sensitization patterns differ across Europe. The use of specific kiwifruit allergens improved the diagnostic performance compared with kiwifruit extract. Sensitization to Act d 1 and living in Iceland are strong risk factors for severe kiwifruit allergy.
Keywords: 80 and over Allergens Antigens; Actinidia Adolescent Adult Aged Aged; Plant Child Europe Female Food Hypersensitivity Humans Immunoglobulin E Male Middle Aged Risk Factors Sensitivity and Specificity Severity of Illness Index Skin Tests Young Adult